2005
DOI: 10.1081/jdi-200056620
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Immunophenotypic Abnormalities in Cellular Immunity of Uremic Patients Undergoing Either Hemodialysis or Continuous Ambulatory Peritoneal Dialysis

Abstract: Replacement therapy may contribute to the quantitative alterations of immune subsets found in HD and CAPD patients compared to normal subjects. We speculate that these changes account, at least in part, for the immune dysregulation observed in patients with chronic renal failure. Analysis of lymphocyte subsets will help the research and the evaluation of the possible causes of immunodeficiency in uremic patients undergoing replacement therapy and will probably contribute to more efficient and preventive strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Comparative analysis of lymphocyte subsets concluded to a significant decrease in B and to a lesser extend NK and CD3 ϩ CD8 ϩ lymphocytes abso- lute numbers before graft in reference to healthy individuals, which may correlate with increased systemic inflammation and lowered immune responsiveness to infectious challenge often reported in hemodialyzed patients (21,22).…”
Section: Discussionmentioning
confidence: 97%
“…Comparative analysis of lymphocyte subsets concluded to a significant decrease in B and to a lesser extend NK and CD3 ϩ CD8 ϩ lymphocytes abso- lute numbers before graft in reference to healthy individuals, which may correlate with increased systemic inflammation and lowered immune responsiveness to infectious challenge often reported in hemodialyzed patients (21,22).…”
Section: Discussionmentioning
confidence: 97%
“…Up to two-thirds of dialysis patients are characterized by a malnutrition-inflammation syndrome [21], and many display disturbances in both innate and adaptive immunity [22-32]. This raises the intriguing hypothesis that Vitamin D deficiency could contribute to the inflammation and immune abnormalities found in this patient population, making it imperative that we understand the etiology of this problem and pursue solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenia and signs of T cell activation have been reported in a lot of the studies [16,17]. In-depth analysis of T cell subsets showed that lymphopenia is particularly prominent in the naïve T cell subset which showed a progressive decline in numbers as the stage of chronic kidney disease increased [2,18].…”
Section: Discussionmentioning
confidence: 99%